Polska wobec kulturowych dylematów i wyzwań „europejskości” - Janowski, Karol B. (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The paper touches upon the issue of the cultural challenges which Poland and the Poles have faced since 1989, in the context of Poland’s integration with Western Europe, which commenced then. The starting point of the analysis is the typology of political cultures of Almond, Verba and Powell. The paper mainly focuses on the manner in which politics is exercised and on Poland’s foreign policy. In the conclusion it attempts to answer the question of whether Poles are culturally close to, or far away from Europe. The complexity of the issue, however, leads to the conclusion that despite the numerous examples the paper refers to, it is exceptionally difficult to answer this question unequivocally.